Tourists' Satisfaction Vs. Residents' Quality of Life in Medium Sized European Cities: A Conjoint Analysis Approach for Cultural Tourism's Impact Assessment - Patrizia Riganti (European Regional Science Association (ERSA), 2006)
This paper discusses the use of conjoint analysis to assess the non market impacts of tourism presence in small and medium sized European cities. It presents the methodological approach developed to this purpose within the EU funded project PICTURE (Pro-active management of the Impact of Cultural Tourism upon Urban Resources and Economies) and its application to the case of the city of Syracuse, Italy. Tourism is one of Europe's largest economic sectors and features among the largest key industries of the 21st century and cultural tourism is one of the forms of tourism that is expected to witness the most important growth in the future. Sustainable cultural tourism strategies have the potential to assist the conservation of local identities, embedded in their respective cultural heritage, while supporting economic growth. However, tourism in cultural sites can also bring negative impacts, which need to be analyzed and assessed. Economic valuation can support decision making in this sector. This paper first discusses to what extent is possible to value in economic terms the positive and negative externalities brought by cultural tourism to heritage destinations, and which are the currently available valuation techniques. Then it focuses on how to manage destinations in a way to limit negative impacts whilst spreading the positive ones in the region. Then it reports the results of a conjoint analysis study on the city of Syracuse, Italy, carried out on a sample of residents and tourists. In particular it looks at the marginal utility associated to attributes interpreting the carrying capacity of the site. Finally, the paper focuses on the potential and limitations of conjoint analysis studies for the above purposes. Conjoint analysis is a non market valuation technique frequently used to place a value on a good. It is a stated-preference method, in the sense that it asks individuals what they would do under hypothetical circumstances, rather than observing actual behaviors on marketplaces, simulating a hypothetical market and analysing stated preferences rather than observing actual market behaviour. In a typical conjoint analysis choice individuals are asked to choose among alternative variants of a good described by a number of attributes. The alternatives differ from one another in the levels taken by two or more of the attributes. The technique assumes the choice between the alternatives is driven by the respondent's underlying utility. Conjoint choice experiments were initially developed by Louviere and Hensher (1982) and Louviere and Woodworth (1983). Conjoint choice experiments have been widely used to value environmental and natural resources, and more recently cultural heritage. Previous research seems to confirm that the technique is flexible enough and can be successfully adapted to the assessment of policy strategies. The paper discusses the steps that should be considered when developing a conjoint choice experiment for similar purposes.
Keywords: 330